Ten Years of TerraSAR-X—Scientific Results - Roth, Achim; Moreira, Alberto; Eineder, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue is a collection of papers addressing the scientific use of data acquired in the course of the TerraSAR-X mission 10 years after launch. The articles deal with the mission itself, the accuracy of the products, with differential interferometry, and with applications in the domains cryosphere, oceans, wetlands, and urban areas.